AKTIVITAS PENGHAMBATAN α-GLUCOSIDASE OLEH KOMBINASI EKSTRAK ETANOLIK BUAH Phaleria macrocarpa (SCHEFF.) BOERL. DAN DAUN Annona muricata LINN. - Era Rahmi; Wulan Tri Wahyuni; Latifah Kosim Darusman; Irma Herawati Suparto (Faculty of Pharmacy, Universitas Gadjah Mada, 2016)
Antidiabetic activities of Phaleria macrocarpa fruits and Annona muricata leaves through α-glucosidase inhibition have been reported. Each extract of the two medicinal plants showed weak α-glucosidase inhibitory activities. The effect of synergies is expected from combining the two extracts. The purpose of this research was to investigate α-glucosidase inhibitory activity of the combination of ethanolic extract of P. macrocarpa fruits and A. muricata leaves and to confirm the presence of different chemical constituents of the most active individual and extracts combination by thin layer chromatography (TLC). Extracts were obtained by maceration method using 96% ethanol. Various concentration of extracts combination was analyzed based on IC50 of the enzyme inhibition of each individual extract. The result showed that α-glucosidase inhibitory activity of each extracts was concentration dependent, with IC50 values of individual extracts of P. macrocarpa fruits and A. muricata leaves were 261.34 and 428.79 μg/mL, respectively. However, the extracts combination with the highest inhibition activity (84.51±0.79%) was obtained at its IC50 of P. macrocarpa fruits and two-third IC50 concentration of A. muricata leaves. The TLC profile of the most active extract combination showed a phytochemical constituent that is also detected in the profile of each individual extract. This can be assumed as a synergistic effect due to increased phytochemical contents of the combined extract.